Coupling process study of lipid production and mercury bioremediation by biomimetic mineralized microalgae. (November 2017) - Peng, Yang; Deng, Aosong; Gong, Xun; Li, Xiaomin; Zhang, Yang
Graphical abstract: Highlights: Novelty biomimetic mineralized microalgae cultivated in Hg(II) wastewater. Mineralized layer enhanced activity of cells in Hg(II) wastewater. Higher lipid yield was observed in mineralized modified cells. Removal of Hg(II) by modified microalgae was proved to be 94.74%. Abstract: Considering the high concentration of mercury in industrial wastewater, such as coal-fired power plants and gold mining wastewater, this research study investigated the coupling process of lipid production and mercury bioremediation using microalgae cells. Chlorella vulgaris modified by biomimetic mineralization. The cultivation was divided in two stages: a natural cultivation for 7 days and 5 days of Hg 2+ addition (10–100 μg/L) for cultivation at different pH values (4–7) after inoculation. Next, the harvested cells were eluted, and lipid was extracted. The fluorescein diacetate (FDA) dye tests demonstrated that the mineralized layer enhanced the biological activity of microalgae cells in Hg 2+ contaminated media. Hg distribution tests showed that the Hg removal capacity of modified cells was increased from 62.85% to 94.74%, and 88.72% of eluted Hg 2+ concentration was observed in modified cells compared to 48.42% of raw cells, implying that more mercury was transferred from lipid and residuals into elutable forms.